Análise de eficientização energética do Prédio Centro de Treinamento - SOUSA, Antonio Ricardo Evangelista de (2018)
Get energy efficiency means using processes and equipment that are more efficient, reducing wasteful energy consumption, both in the production of goods and in the provision of services, without thereby affecting their quality. And essential to preserve and encourage the efficient use of electricity in all socio-economic sectors in Brazil, is of great importance for parents to final adoption of energy saving measures and the consequent impact of these actions. Thus, in this work we present a case study analysis and energy efficiency in the Training Center building belonging to Eletrobras Eletronorte-located in the permanent village of Tucuruí - PA. To this end, energy analysis of their lighting system are performed by using the software DIALUX EVO, and study of the building and energy pricing methodology and following the recommendations provided by PROCEL. Therefore, based on the results acquired by the developed studies, expected to achieve reduction in the use of electricity and rationalization of consumption by determining inefficient processes and optimization proposals.